Electrical muscle stimulation induces an increase of VEGFR2 on circulating hematopoietic stem cells in patients with diabetes - Hidmark, Asa S.; Fleming, Thomas; Volk, Nadine; Eckstein, Volker; Gröner, Jan; Kopf, Stefan; Nawroth, Peter Paul; Oikonomou, Dimitrios (Clinical therapeutics, 2017)
Purpose: External electric muscle stimulation (EMS) of the thigh muscles was found to reduce pain resulting from diabetic neuropathy (DN), a vascular complication of diabetes. This study investigated circulating hematopoietic stem cells (HSCs) after EMS treatment. Impaired function of HSCs and the subpopulation endothelial progenitor cells (EPCs), important for neovascularization and endothelial repair, has been associated with DN. Methods: Twenty-four patients with painful DN were treated 3 times with EMS over a period of 1 week. Blood samples were collected before and after the first EMS treatment. Before a fourth treatment, neuropathic pain was evaluated and a third blood sample was collected. Cells were used for flow cytometry. Findings: Patients with painful DN reported that the pain decreased after 3 times of 1-hour treatments with EMS (Neuropathy Symptom Score: from 8 to 6, P = 0.001; Neuropathy Disability Score: from 5.5 to 5, P = 0.027, n = 24). At the end of the study, diastolic blood pressure had decreased from 80 to 70 mm Hg (P = 0.043), and plasma adrenaline and noradrenaline metabolites metanephrine and normetanephrine were reduced (both P ≤ 0.01; n = 21). A single EMS treatment caused an immediate and transient decrease in the frequency of CD34+ HSCs in circulation (-20%; P < 0.001; n = 27). In 9 of the patients with DN, the proportion of HSCs expressing vascular endothelial growth factor receptor 2 (VEGFR2; defining the HSCs as EPCs) increased by 36% (P = 0.011) after EMS treatment. Proteins required for binding to endothelium (junctional adhesion molecule A and CD31), homing toward hypoxic tissue (C-X-C chemokine receptor type 4), and endothelial differentiation (CD31) were increased on HSCs immediately after EMS treatment. An increased frequency of VEGFR2 expression was also observed on HSCs of 6 healthy control volunteers (34%; P = 0.046) after EMS treatment, but not after sham treatment. Implications: Three EMS treatments decreased symptoms of pain caused by DN and reduced diastolic blood pressure and biomarkers of stress. A single EMS treatment increased molecules mediating attachment and differentiation on the surface of HSCs in circulation. We hypothesize that the EMS-induced increase in surface attachment molecules on the HSCs caused the HSCs to leave circulation and that EMS treatment improves the function of HSCs and EPCs in vivo.
Available online 27 May 2017
Gesehen am 15.06.2018